Sustainable Education Systems For The Unfortunate In South Sulawesi - Andi Rasyid Pananrangi (Universitas Negeri Malang, 2016)
The aim of this paper was (1) to explain some basic issues faced by the education policy makers in South Sulawesi, including the introduction of school fees and the private provision of schools; (2) to outline the relation between planning and budgeting for the educational policy objectives on the one hand and the economic planning and management of resources on the other; (3) to discuss the influence of this policy for the unfortunate in obtaining education. This study was carried in South Sulawesi. A descriptive approach was used in this study. The data were collected through library research and observation. The obtained data were then analyzed and presented descriptively. The results show that the available approach is not adequate to accommodate and to provide the opportunity of education for the unfortunate in South Sulawesi. The full or partial replacement of annual incremental planning and budgeting systems were still less appropriate to current problems. Reforms should also take full account of the need to strengthen a potentially beneficial relationship between the state and the private sectors.